Penguatan Civic Dispotition Melalui Pendidikan Pancasila Dalam Meningkatkan Sikap Domokratis Siswa Kelas 4 Sekolah Dasar - Arni Malau, Rizki Wahida; Resty, Muthia; Hasibuan, Akhirunnisa; Maghfirah, Addina; Perangin-angin, Reh Bungana Beru (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2025)
This study aims to analyze the strengthening of civic disposition through Pancasila Education subjects in improving the democratic attitudes of fourth-grade elementary school students. Civic disposition is an essential component in citizenship education that includes attitudes, values, and characters needed to become good citizens in a democratic system. This study uses a qualitative approach with a case study method conducted at SDN 101765 Bandar Setia, Bandar District, Simalungun Regency, North Sumatra. Data collection was carried out through observation, in-depth interviews, and documentation. The results showed that the initial condition of fourth-grade students' civic disposition was still at a level that needed serious attention, with only 35% of students actively participating in class discussions. The implementation of Pancasila Education learning through group discussions, problem-based learning, and role-playing methods proved effective in developing students' democratic attitudes. The integration of democratic values such as tolerance, responsibility, and deliberation in learning was not only taught as theoretical concepts, but also practiced in the context of students' real lives. Supporting factors for success include teacher commitment, principal support, suitability to students' cognitive developmental stages, and parental involvement. This study emphasizes the importance of participatory and democratic Pancasila education learning in forming the foundation of civic disposition from elementary school age